Charge-compensated codoped pseudohexagonal zinc selenide nanosheets towards enhanced visible-light-driven photocatalytic water splitting for hydrogen production. (6th October 2021) - Ni, Chen; Fu, Can; Wang, Biao; Yuan, Hongkuan; Chen, Hong
Abstract: Two-dimensional (2D) pseudohexagonal ZnSe ( h -ZnSe) nanosheet has been sythesized and demonstrated to be a stable, cut-price and high-efficiency photocatalyst under the irradiation of ultraviolet light. Herein, we use hybrid density functional theory to rationally design the charge-compensated codoped h -ZnSe sheets, which are simulated by substituting Sb for Se atom, and Sc or Y for Zn atom, for visible-light-driven photocatalytic water splitting to produce hydrogen. It is demonstrated that the Sc–Sb and Y–Sb codoped sheets are energetically favorable compared with Sc, Y, Sb-monodoped sheets because dopants have strong Coulombic interactions with other atoms, and moreover, have the effectively reduced bandgap, the larger absorption region of visible light, and appropriate band edges positions with respect to the water redox level. Meanwhile, compared to monodoped sheets, the codoped sheets do not introduce charge-imbalance defects or unoccupied impurity states which promote the electron-hole recombination. Furthermore, the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are easier driven by photogenerated carriers due to the largely reduced overpotentials and ample active sites on the codoped sheets. Thus, the Sc–Sb and Y–Sb codoped h -ZnSe sheets can be promising photocatalysts for visible-light-driven water decomposition to generate hydrogen. Graphical abstract: Image 1 Highlights: Sc-or Y-Sb passivated codoping can effectively reduce band gap of pseudohexagonal ZnSe sheet. Codoped ZnSe sheets have suitable positions of band edges with respect to the water redox potentials. Codoping can promote the visible light absorption of ZnSe sheet. Codoping can reduce the overpotential of ZnSe sheet for OER and HER. Sc-or Y-Sb codoped ZnSe sheets are promising visible-light-driven photocatalyst.